Soil Vulnerability Levels based on Microtremor Data using the HVSR method in the Old City Area of Semarang - Supriyadi Supriyadi; Wahyu Humam Muttaqin; Khumaedi Khumaedi; Sugiyanto Sugiyanto (Universitas Sebelas Maret, 2022)
Kota Lama Semarang with the Dutch colonial era relics is currently used as a cultural heritage tourist spot. As a cultural heritage tourism place, it is necessarily aware of the potential for earthquake disasters due to active faults and volcanic eruptions, as well as the phenomenon of land subsidence caused by geological conditions of young alluvium. One of the geophysical techniques to determine subsurface structure is microtremor measurement. This study aims to determine vulnerability level based on dominant frequency, amplification, and seismic vulnerability index using HVSR analysis in Kota Lama area. Microtremor data measurement contained 11 points with a data retrieval duration of 30 minutes. The results of microtremor data analysis obtained dominant frequency values of 7.03 - 19.36 Hz, amplification of 0.72 – 3.7, and seismic vulnerability index of 0.074 – 0.95. Based on the parameters, it can be concluded that the Kota Lama Semarang area has a low level of vulnerability.